MEMBANGUN MAHASISWA YANG KREATIF DAN PRODUKTIF: SOSIALISASI PROGRAM KAMPUS MENGAJAR DAN PENULISAN ARTIKEL ILMIAH - Pandu Rudy Widyatama; Putresa Eka Irmandini (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2024)
This service activity aims to increase students' creativity in the Teaching Campus Program and their skills in writing scientific papers. The Teaching Campus Program provides opportunities for students to apply the knowledge learned in college to the surrounding world of education, as well as hone practical skills that are important in the world of work. In addition, students also need to be equipped with knowledge and understanding of the importance of scientific writing as a means of sharing the knowledge they have. The method used in this activity is Participation Action Research (PAR), which integrates theory with practice that has been carried out. The results of the service showed a considerable change in the students' ability to organize ideas, formulate scientific arguments, and increase their confidence in writing, which was seen from the number of subjects who were before and after the training. The success of this activity will also affect the development of students' character in facing the challenges of the world of work. Further developments in scientific writing training and the use of technology can have a wider impact.